PENGARUH SISTEM PENYIMPANAN LOGISTIK UMUM TERHADAP EFEKTIVITAS KERJA DI GUDANG SUB BAG KERUMAHTANGGAAN DAN PERLENGKAPANDI RSUD AL-IHSAN PROVINSI JAWA BARAT - Nurul Dwi Ariyani; Ima Yohana (INFOKES (Informasi Kesehatan), 2019)
This study aims to find out about the influence of general logistics storage system against to the effectiveness of the work in the Warehouse Sub-Division Domesticity And Equipment In Rumah Sakit Umum Daerah Al-Ihsan West Java Province. This research uses method assosiative with quantitative approach, data analysis with techniques validity test, reliability test, Spearman rank correlations test, and coefficience determination test. Data collected by observation, questionnaires, and study literature by subject of research is the warehouse in sub-division domesticity and equitment in rumah sakit umum daerah Al-Ihsan West Java Province as many as 10 peoples. The results of this research shows the correlation is 0.975 which that mean there is a very strong and positive relationship between general logistics storage variable (X) with effectiveness of work variable (Y), and the result of the influence between general logistics storage variable (X) to the quality of effectiveness of the work variable(Y) is 95.6% this means that the very strong influence and 4.4% the rest is influenced by other factors. From this research there is a problem such as : (1) the regulation of the layout storage shed have not optimal; (2) the onccurrence of a general logistics stack such as (mold) on a storage rack; (3) found a difference between physical stock with the stock opname. The advices that given on this research are : (1) provide an expansion of warehouse; (2) provide an addition of base for goods on the floor; (3) expected there is a repairing of SIM RS application like barcode.